2015
DOI: 10.3892/or.2015.4150
|View full text |Cite
|
Sign up to set email alerts
|

Subpath analysis of each subtype of head and neck cancer based on the regulatory relationship between miRNAs and biological pathways

Abstract: Abstract. The aim of the present study was to explore the potential mechanisms involved in each subtype of head and neck squamous cell carcinoma (HNSCC) via subpath analysis and to investigate their relevance in the prevention of HNSCC. Gene expression profiles of GSE6631 and GSE39366 containing 44 and 168 HNSCC samples, respectively, were downloaded from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) from samples in GSE6631 and GSE393666 were screened using the Detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Moreover, other studies have investigated the potential roles of miR-506 in cancer. Through subpathway analysis of each subtype of head and neck squamous cell carcinoma (HNSCC), An et al demonstrated that several miRNAs (miR-506, let-7a, miR-1, miR-206, miR-153, and miR-519a) and their target genes play crucial roles in the prevention of HNSCC via regulating several distinct pathways [ 62 ]. Li et al reported that miR-506 was the most significant miRNA screened by a bioinformatics strategy in prostate cancer and was found to regulate genes including ITGB1 and ITGB3 by binding the target sequence GUGCCUU [ 63 ].…”
Section: Other Tumor Typesmentioning
confidence: 99%
“…Moreover, other studies have investigated the potential roles of miR-506 in cancer. Through subpathway analysis of each subtype of head and neck squamous cell carcinoma (HNSCC), An et al demonstrated that several miRNAs (miR-506, let-7a, miR-1, miR-206, miR-153, and miR-519a) and their target genes play crucial roles in the prevention of HNSCC via regulating several distinct pathways [ 62 ]. Li et al reported that miR-506 was the most significant miRNA screened by a bioinformatics strategy in prostate cancer and was found to regulate genes including ITGB1 and ITGB3 by binding the target sequence GUGCCUU [ 63 ].…”
Section: Other Tumor Typesmentioning
confidence: 99%
“…Study of ER+ breast cancer demonstrated that miR-519a served as an oncomir by regulating tamoxifen resistance and its elevated expression was correlated with poor survival of breast cancer patients [13] . Statistical analysis of Gene Expression Omnibus (GEO) database showed that miR-519a was involved in the progression of head and neck squamous cell carcinoma [14] . However, the clinical significance and functional role of miR-519a in HCC were still undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the type V collagen assembled by COL5A1 may mediate interleukin products and further regulate immune responses, which play especially important roles in auto-immunity (Yamada et al, 2009; Sullivan et al, 2017). Another possible mechanism is COL5A1 ’s involvement in extracellular matrix (ECM) formation (An et al, 2015). CLO5A1 has been verified to be correlated with several types of cancer (Fan et al, 2016; Zhao et al, 2016; Li et al, 2017a; Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%